Research Progress on the Correlation between Gut Microorganisms and Gastrointestinal Diseases - Li, Yuanyuan; Wu, Xiaokang (Journal of Contemporary Medical Practice, 2024)
The intestinal microbiota refers to the complex community of microorganisms present in the human digestive tract. With the development of high-throughput sequencing technologies such as 16SrRNA gene sequencing and metagenomic sequencing, the intestinal microbiota has been shown to be closely related to gastric cancer and colorectal cancer. At the same time, a series of studies have been conducted to explore the intestinal microbiota as a new type of non-invasive biological marker. This article summarizes the research on the intestinal microbiota of gastric cancer and colorectal cancer, and explains the changes in the intestinal microbiota when the disease occurs, so as to provide new ideas for finding potential molecular targets for the prevention, treatment, and intervention of tumors.